Integration of Technology in Arabic Language Pedagogy: Challenges and Opportunities for Modern Curriculum Development - Jamil, Muhammad Abdun; Abdullayev, Devin (UIN Mahmud Yunus Batusangkar, Indonesia, 2024)
This study explores the challenges and opportunities of integrating technology into Arabic language pedagogy, in line with the rapid development of educational technology in the digital era. Conducted at STIT Bustanul Ulum, this research highlights how technology can enhance the accessibility and interactivity of learning. However, its implementation still faces numerous obstacles, such as limited infrastructure and low digital literacy among educators. The aim of this research is to identify the main challenges encountered and the potential uses of technology to improve the effectiveness of Arabic language instruction. This study employs a descriptive qualitative method, collecting data through interviews, observations, and document analysis at STIT Bustanul Ulum. The findings reveal that although technology offers significant benefits in supporting more personalized and adaptive learning, its application is hindered by infrastructure limitations and insufficient teacher training. The study recommends stronger policy support and more structured curriculum development to maximize technology integration in Arabic language education.